Exploring the Influence of Brand Coolness on Brand Love and Brand Engagement: Systematic Literature Review - Mega Yuliana , Lucia; Kusumawati, Andriani; Luthfi Imam Fahrudi, Agung Nugroho (FIA UB, 2025)
This study aims to explain and provide an overview of brand coolness that affects brand love and engagement. This research uses a Systematic Literature Review with the PRISMA method to synthesize scientific evidence to answer specific research questions. The database used comes from journals on Google Scholar. The results show that brand reliability, social value and emotional resonance are three aspects that can form brand coolness that positively affects brand love, namely in terms of brands, society and consumers themselves. Brand coolness has a positive impact on brand engagement through usability, originality in products and subcultural appeal. This research adds theoretical updates about several points that need to be considered for brand existence to survive in consumers, which need to be considered with emotional involvement with the brand. This research contributes to developing literature on brand coolness indicators to influence brand love and engagement and help brands design management strategies to present the value of coolness more effectively. Future research can examine consumer reactions to brand coolness, brand prestige, and brand authenticity to further understand brands today with consumers' rapidly changing consumption patterns and lifestyles.